Low energy availability followed by optimal energy availability does not benefit performance in trained females - Oxfeldt, M.; Marsi, D.; Christensen, P. M.; Andersen, O. E.; Johansen, F. T.; Bangshaab, M.; Risikesan, J.; Jeppesen, J. S.; Hellsten, Y.; Phillips, S. M.; Melin, A. K.; Ørtenblad, N.; et al. (Medicine & Science in Sports & Exercise, 2024)
Purpose Short periods of reduced energy availability are commonly undertaken by athletes to decrease body mass, possibly improve the power-to-mass ratio, and enhance physical performance. Our primary aim was to investigate the impact of 10 d of low energy availability (LEA) followed by 2 d of optimal energy availability (OEA) on physical performance parameters in trained females. Second, physiological markers at the whole-body and molecular level related to performance were evaluated.